2008
DOI: 10.1097/iae.0b013e3181669504
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 Neovascularization

Abstract: The neovascularization in RAP may originate not only from deep retinal capillaries but also from the choroid. We therefore propose the more descriptive term "Type 3 neovascularization" for this entity to emphasize the intraretinal location of the vascular complex and distinguish this type from the two types of neovascularization previously described by J. Donald Gass in his classic text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(69 citation statements)
references
References 19 publications
1
62
0
1
Order By: Relevance
“…It has been hypothesized that RAP lesions might respond more rapidly to intravitreal anti-VEGF therapies [1]. This is in accordance with our results, considering that 81.5% of the total visual improvement and 85% of the total CMT reduction occurred during the first post-operative month, after one intravitreal injection of ranibizumab.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It has been hypothesized that RAP lesions might respond more rapidly to intravitreal anti-VEGF therapies [1]. This is in accordance with our results, considering that 81.5% of the total visual improvement and 85% of the total CMT reduction occurred during the first post-operative month, after one intravitreal injection of ranibizumab.…”
Section: Discussionsupporting
confidence: 92%
“…Freund et al [1] reported rapid resolution of the intraretinal edema, hemorrhage, and neovascular lesion of three patients with RAP lesions treated with a single injection of intravitreal ranibizumab.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our best knowledge, there is only one study of ranibizumab as single-dose monotherapy. This study included only early cases of RAP (stage I and II), and authors reported either complete response or spontaneous resolution without treatment [32]. However, long-term data confirming the sustainability of these positive initial results are not available.…”
Section: Discussionmentioning
confidence: 99%